The Effect of English Children's Songs on Students Pronunciation Enhancement - salisah, indi rahmawati; Suryadi, Suryadi; Pahamzah, Jhon (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract The aim of this study was to investigate the influence of children's song media on the enhancement of English pronunciation skills among fourth-grade students at MI Bina Ummat. The research employed a single-group pretest and posttest design, adopting an experimental approach. Thirty children from the fourth grade of MI Bina Ummat comprised the study population. The t-test was used in the analysis of this research data. The findings of the study showed that children's song media had a significant impact on students' English pronunciation, with a t-count of 8.101 > t-table of 2.042. The average value was 54.00 for pre-test data and 80.64 for post-test data. The difference in the average value is 24.64, representing a percentage increase of 42%. These results illustrate the extent of the change in students' pronunciation ability. Consequently, the use of children's song media is demonstrated to have a positive effect on improving English pronunciation skills among fourth-grade students at MI Bina Ummat, as indicated by these findings. Keywords: english pronouncation, english children's song media Abstrak Â Tujuan dari penelitian ini adalah untuk menyelidiki pengaruh media lagu anak-anak terhadap peningkatan keterampilan pengucapan bahasa Inggris di kalangan siswa kelas empat di MI Bina Ummat. Penelitian ini menggunakan desain pretest dan posttest kelompok tunggal, mengadopsi pendekatan eksperimental. Tiga puluh siswa kelas empat MI Bina Ummat menjadi populasi penelitian. Uji t digunakan dalam analisis data penelitian ini. Hasil penelitian menunjukkan bahwa media lagu anak-anak memiliki dampak signifikan pada pengucapan bahasa Inggris siswa, dengan nilai t hitung sebesar 8,101 > t tabel sebesar 2,042. Nilai rata-rata adalah 54,00 untuk data pretest dan 80,64 untuk data posttest. Perbedaan nilai rata-rata adalah 24,64, yang mencerminkan peningkatan persentase sebesar 42%. Hasil ini menggambarkan sejauh mana perubahan kemampuan pengucapan siswa. Oleh karena itu, penggunaan media lagu anak-anak terbukti memiliki efek positif dalam meningkatkan keterampilan pengucapan bahasa Inggris di kalangan siswa kelas empat di MI Bina Ummat, sebagaimana ditunjukkan oleh temuan ini. Kata Kunci: pengucapan bahasa inggris, media lagu anak bahasa inggris